Social Policy Experience In Indonesia: Case Study On Unconditional Cash Transfer Program - Sugandi, Yogi Suprayogi (Departemen Administrasi Publik Fakultas Ilmu Sosial dan Ilmu Politik Universitas Padjadjar, 2017)
This Article is intended to the poverty incidence that occurred in Indonesia in 2005 and 2008 as the impact of rising world oil prices that led to the unconditional cash transfer program UCT (Bantuan Langsung Tunai (BLT) i.e Indonesia literate) was launched in Indonesia. BLT program is one program that was launched by the Indonesian government in early 2005 and mid 2008. Unconditional cash transfer program is one of the social policy given to the poor as a way to reduce the impact of rising world oil prices that could affect the purchasing power of the poor in Indonesia. This program circulate the money of approximately US 10/month is regarded as an aid that is âgiving charityâ to the poorin Indonesia. This article also will show some of the BLT program as one of the social policy in Indonesia. The various obstacles encountered during this policy and also someeconomic and social problems encountered in this program, starting from the problems of counting the poor community, the implementation of the program until the end of thisBLT program. This will be a descriptive writing by describing a variety of archival and field data the government and conducted by the author. It is to intended the readers toknow how social policy was implemented in Indonesia as an experience.